2015
DOI: 10.4328/jcam.2262
|View full text |Cite
|
Sign up to set email alerts
|

Results in the Treatment of Tibial Diaphyseal Fractures with Expandable Intramedullary Nails

Abstract: ÖzetAmaç: Tibia şaft kırıklarında genişleyebilir intramedüller çivilerin klinik kullanımı, etkinliği ve kısa dönem sonuçları araştırıldı. Gereç ve Yöntem: Tibia şaft kırığı olan 22 hasta (9 kadın, 13 erkek; ort. yaş 33; dağılım 21-65) çalışmaya alındı. Tüm hastalarda kapalı kırık vardı. Tüm hastalarda genişleyebilir intramedüller çiviyle internal tespit uygulandı. Kırık oluşumundan ameliyata kadar geçen süre ortalama 2,5 gün (dağılım 12 saat-5 gün) idi. Sonuçlar JohnerWrush ve Kalstrom-Olerud ölçütlerine göre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the literature, we observed similar results in the healing time of fractures repaired using expandable IM nails. Ghafil et al [12] reported a mean healing time of 3.9 months, Kaapor et al [5] reported 4.8 months, while Serbest et al [16] reported 4.2 months. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we observed similar results in the healing time of fractures repaired using expandable IM nails. Ghafil et al [12] reported a mean healing time of 3.9 months, Kaapor et al [5] reported 4.8 months, while Serbest et al [16] reported 4.2 months. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%